Analisis Finansial Usaha Ternak Ayam Ras Petelur (Layer) di Kecamatan Gading Rejo Kabupaten Pringsewu - Eka Kurniawan; Asek A; Herawati M (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2018)
The aim of this study is to determine the financial feasibility of laying fullet business (layer) in District Gading Rejo Pringsewu Regency. The research method used in this research is survey method. This method is a method by using samples taken from the population with a data collection tool in the form of a quisioner. Data analysis techniques using business feasibility analysis including R/ C ratio and Break Event Point (BEP). The conclusion of this research is business laying pullet (layer) financially is feasible. This is indicated from the results of feasibility analysis by using the analysis of R/C ratio and BEP, obtained the value of R/C ratio > 1 and BEP value of production and price < actual production value and price. Keywords: Laying chicken, R/C Ratio, Break Event Point